You Are What You Consume - Ahmed, Jubayer (Global Disclosure of Economics and Business, 2015)
The main objective of this study is to analyze the impact of individual’s self-concept in consumption pattern. Consumers intentionally or unintentionally consume different products and services during their lifetime and their consumption pattern or preferences are closely associated with their sense of self.  Similarly, consumers tend to avoid commodities or services that contradict with their self-image. A number of empirical studies have been analyzed further to investigate the influence of self- concept on brand or product selection.